Providing Delay Guarantees to Time-Sensitive Traffic by Scheduling using OFDMA with Deadline Estimation While Avoiding Best-Effort Traffic Starvation - Muhammad Inamullah (International Journal of Intelligent Systems and Applications in Engineering, 2020)
OFDMA is introduced to WLANs in the ax amendment of the IEEE 802.11 standard. It makes the WLAN a closed-loop system, where AP assigns OFDMA resource units to the STAs for uplink transmissions. The scheduling algorithms generally optimize throughput by minimizing upload time. For time-sensitive traffic, the time-critical packets that miss their deadlines become useless, even if overall upload time is minimized. To provide schedules that prioritize the STAs for transmission whose traffic has earlier deadlines, the AP needs to know the packet deadlines in the queue of each STA. Since STAs do not provide any information on the expiration time of the packets they send to the AP, we give an algorithm to estimate on the AP side the deadlines of HOL packets waiting at STAs and make a scheduling decision that minimizes the number of packets dropped due to expired deadlines. In doing so, the best-effort traffic is also scheduled to prevent its starvation. Compared to the number of packet drops with the traditional approach of throughput optimization, our approach shows up to a six-fold reduction in packet drops due to missed deadlines at the STAs. Our approach also avoids starvation of the best-effort traffic.